(Pentamethylcyclopentadienyl)cobalt(III)‐Catalyzed C–H Bond Functionalization: From Discovery to Unique Reactivity and Selectivity. Issue 8 (16th March 2017) - Yoshino, Tatsuhiko; Matsunaga, Shigeki
Abstract: High‐valent (pentamethylcyclopentadienyl)cobalt(III) [Cp*Co(III)] catalysts were found as inexpensive alternatives to (pentamethylcyclopentadienyl)rhodium(III) [Cp*Rh(III)] catalysts in the field of C—H bond functionalization, and applied to a variety of transformations. In this review, after the discovery and early examples of Cp*Co(III)‐catalyzed C—H bond functionalization are summarized, the unique reactivity and selectivity of Cp*Co(III) and the differences between the cobalt and rhodium catalysis are intensively discussed. Such differences are assumed to be caused by the lower electronegativity, hard nature, and smaller ionic radius of cobalt. Abstract :